Pathogenesis of microbial keratitis - Lakhundi, Sahreena; Siddiqui, Ruqaiyyah Bano *; Khan, Naveed Ahmed * (Elsevier, 2016)
Microbial keratitis is a sight-threatening ocular infection caused by bacteria, fungi, and 2 protist pathogens. Epithelial defects and injuries are key predisposing factors making the eye 3 susceptible to corneal pathogens. Among bacterial pathogens, the most common agents 4 responsible for keratitis include Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus 5 pneumonia and Serratia species. Fungal agents of corneal infections include both filamentous as 6 well as yeast, including Fusarium, Aspergillus, Phaeohyphomycetes, Curvularia, Paecilomyces, 7 Scedosporium and Candida species, while in protists, Acanthamoeba spp. are responsible for 8 causing ocular disease. Clinical features include redness, pain, tearing, blur vision and 9 inflammation but symptoms vary depending on the causative agent. The underlying molecular 10 mechanisms associated with microbial pathogenesis include virulence factors as well as the host 11 factors that aid in the progression of keratitis, resulting in damage to the ocular tissue. The 12 treatment therefore should focus not only on the elimination of the culprit but also on the 13 neutralization of virulence factors to minimize the damage, in addition to repairing the damaged 14 tissue. A complete understanding of the pathogenesis of microbial keratitis will lead to the 15 rational development of therapeutic interventions. This is a timely review of our current 16 understanding of the advances made in this field in a comprehensible manner. Coupled with the 17 recently available genome sequence information and high throughput genomics technology, and 18 the availability of innovative approaches, this will stimulate interest in this field.